2021
DOI: 10.1038/s41379-021-00790-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with myocardial SARS-CoV-2 infection, myocarditis, and cardiac inflammation in patients with COVID-19

Abstract: COVID-19 has been associated with cardiac injury and dysfunction. While both myocardial inflammatory cell infiltration and myocarditis with myocyte injury have been reported in patients with fatal COVID-19, clinical-pathologic correlations remain limited. The objective was to determine the relationships between cardiac pathological changes in patients dying from COVID-19 and cardiac infection by SARS-CoV-2, laboratory measurements, clinical features, and treatments. In a retrospective study, 41 consecutive aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
103
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 41 publications
11
103
1
5
Order By: Relevance
“…Despite concern for myocarditis in both non-critical and critically ill patients, biopsy proven myocarditis remains rare and inconsistent across autopsy reports. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 , 34 ] In this cohort, only two (4.0%) patients met criteria for a focal myocarditis – with the cause of death in these patients attributed to COVID-19 pneumonia with bacterial coinfection and COVID-19 pneumonia with pulmonary embolism. In the two patients in which the cause of death was listed as a dilated cardiomyopathy, neither patient exhibited a lymphocytic inflammatory infiltrate within the heart, and findings were most consistent with chronic hypertensive and atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 95%
“…Despite concern for myocarditis in both non-critical and critically ill patients, biopsy proven myocarditis remains rare and inconsistent across autopsy reports. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 , 34 ] In this cohort, only two (4.0%) patients met criteria for a focal myocarditis – with the cause of death in these patients attributed to COVID-19 pneumonia with bacterial coinfection and COVID-19 pneumonia with pulmonary embolism. In the two patients in which the cause of death was listed as a dilated cardiomyopathy, neither patient exhibited a lymphocytic inflammatory infiltrate within the heart, and findings were most consistent with chronic hypertensive and atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 95%
“…Myocardial injury may play a significant role in predicting poor outcomes in patients without a known history of chronic coronary syndromes 35 . However, a very recent study shows abundant evidence of heart damage in COVID-19 patients 36 . This retrospective study that examined 41 autopsies of COVID-19 patients concluded that cardiac tissues of the 30/41 cases harboured the SARS-CoV-2 virus in their hearts, while others have experienced inflammation of the sac surrounding the heart 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Sars-COV-2 gains access to cells by binding to the ACE2 receptor, which is expressed ubiquitously is many tissues (21,22). There is histopathologic evidence to suggest that Sars-COV-2 infects endothelial cells and possibly inducing endothelial dysfunction (23,24). There is also a well-known tendency towards thrombosis in patients with moderate-to-severe COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%